2007
DOI: 10.1080/02786820601064857
|View full text |Cite
|
Sign up to set email alerts
|

Particle Levitation Due to a Uniformly Descending Flat Object

Abstract: This article presents analytical and computational fluiddynamics (CFD) solutions of the unsteady flow resulting from a horizontal circular disk moving downward at a constant velocity toward a horizontal floor seeded with spherical micro-particles, and the effect of this flow on particle detachment and levitation. The selected configuration is a simplification of numerous practical applications in which particle resuspension is important, for example a foot or an object impacting a dusty floor, or a squeeze fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…In addition, the turbulence of the airflow may vary considerably over different ventilation duct elements, such as duct bends and irregularly shaped flex duct. For resuspension from flooring, airflow associated with the downward foot motion is likely very impulsive with high acceleration (Khalifa and Elhadidi 2007). Resuspension due to human activity may also generate additional removal forces, such as mechanical forces, due to surface vibrations, and electrostatic forces associated with the walking process (Gomes et al 2007;Hu et al 2008;Qian and Ferro 2008).…”
Section: Limitations Of the Present Investigationmentioning
confidence: 98%
“…In addition, the turbulence of the airflow may vary considerably over different ventilation duct elements, such as duct bends and irregularly shaped flex duct. For resuspension from flooring, airflow associated with the downward foot motion is likely very impulsive with high acceleration (Khalifa and Elhadidi 2007). Resuspension due to human activity may also generate additional removal forces, such as mechanical forces, due to surface vibrations, and electrostatic forces associated with the walking process (Gomes et al 2007;Hu et al 2008;Qian and Ferro 2008).…”
Section: Limitations Of the Present Investigationmentioning
confidence: 98%
“…Kubota et al (2009) and Kubota and Higuchi (2013) reported jet velocities of approximately 2-3 m/s associated with the downward foot motion, Gomes et al (2007) reported peak air velocities of 1.5-2 m/s associated with walking-related airflow near the floor, and a modeling study by Zhang et al (2008) found a maximum radial velocity of 18.3 m/s beneath the foot. Additionally, the airflows are likely very impulsive with high acceleration (Khalifa and Elhadidi 2007), and an important factor affecting resuspension (Ibrahim et al 2003).…”
Section: Hard Flooringmentioning
confidence: 99%
“…The first is related to human motion such as walking ($1 m=s), which is too low to detach microparticles. The second is caused by squeezing the fluid under the foot approaching the floor, which was shown to be much higher (10 s of m=s)-exceeding the critical velocity needed to detach even micron-sized particles (Khalifa and Elhadidi 2007). Similarly, for objects falling under the effect of gravity (books from desks for instance), the velocity at impact, V, and the resulting vertical motion created by the falling object are typically too low to detach an attached microparticle (V < 5 m=s), however, the lateral velocity underneath the falling object generated by air film squeezing far exceeds the critical velocity needed to detach even small submicron particles.…”
Section: Introductionmentioning
confidence: 97%